MITA interleaver for OFDM-IDMA and SCFDMA-IDMA techniques using QPSK modulation over PLC - Priyanka Agarwal; Manoj K. Shukla (Bulletin of Electrical Engineering and Informatics, 2022)
The paper aims to examine the performance of multiplicative interleaving with tree algorithm (MITA) interleaver for grouped IDMA systems i.e., SCFDMA-IDMA and OFDM-IDMA, using QPSK modulation over powerline channel. The prime objective is to evaluate the MITA algorithm for its complexity and throughput over multiple communication systems so that it fulfills the requirements of 5G technology. Higher throughput and low complexity are achieved by the structure of MITA interleaver, in which more users are allotted interleavers per clock cycle as compared to existing interleavers primarily, random, tree, and FLRITI. The analysis is carried out in MATLAB environment for varying parameter values such as data length and user count and is plotted in terms of bit error rate (BER). Next, the effect of Convolutional coding is observed on grouped IDMA systems and lastly comparison in terms complexity is carried out. The simulation results over grouped IDMA systems show that MITA interleaver has better BER performance than FLRITI for large user count and the response further improves with greater number of users. The comparison of interleavers in terms of complexity reveals that MITA has lower complexity than FLRITI. Thus, MITA interleaver can be preferred over FLRITI and is a better option to be implemented in 5G technologies.